Investigating and Comparing the Effects of Vasopressin Injection around Uterine Myoma and Rectal Misoprostol Injection in open Myomectomy Surgery to Reduce Bleeding: A Randomized Interventional Study - Ghahiri, Masih; Kordjazi, Saeedeh; Ghahiri, Ataollah (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to compare the effects of vasopressin injection around the uterine myoma in open myomectomy with misoprostol rectal surgery to reduce bleeding during the surgery and the level of changes in hemoglobin. In a clinical trial study, 66 patients who were candidates for open myomectomy were randomly divided into two groups (each group included 33 patients). The first group received 400 µg of misoprostol 30 minutes before rectal surgery, and the second group received a 20-unit vasopressin ampoule in 19 ml of dissolved normal saline 30 minutes before the surgery. The bleeding volume and hemoglobin level before and after the surgery were measured in two groups and compared with independent and paired t-tests. The mean bleeding volume in the two misoprostol and vasopressin groups was 199.4 ± 370.9 and 261.5 ± 120.3 ml, respectively. The mean lost blood was lower in the vasopressin group (p=0.009). The mean changes in hemoglobin level in the misoprostol and vasopressin groups were 1.68 ± 0.63 and 1.3 ± 0.55 g / dl, respectively, and the difference between two groups was significant (p = 0.01). Based on the results of our study, vasopressin seems to be more effective than misoprostol in controlling bleeding during myomectomy, but due to inconsistencies in the results of different studies, further studies on these two drugs are recommended to determine the most effective drug in controlling bleeding during the myomectomy surgery.